Esquemas de percepção das relações sociais pelas classes populares e a ordem social no Haiti de 1986 a 2018 : uma explicação da inexistência de um "Movimento Popular" no campo político haitiano. - Lucien, Louis Jacksonne (2020)
This research work has as a general objective to analyze the interference of the perception patterns of social relations by the popular classes in the difficulty of constituting a popular movement for a transformation of the social order in Haiti from 1986 to 2018. Thirty years ago, under the impetus of various factors, and a strong presence of the popular social categories, the Haitian civil society confronted the dictatorship of the Duvaliers, while claiming the construction of a democratic society and less inegalitarian. According to the majority reading, more than the fall of the dictatorship that will occur in 1986, this movement aimed at a total transformation of the social structure producing mass exclusion that is Haitian society. However, today many researchers make, on the one hand a statement of failure and even speak on the other hand, the lack of a progressive social movement in Haiti. Indeed, in spite of the permanence of the societal crisis and the worsening of their living conditions, the popular social categories do not manage to constitute a "popular movement" with a view to a transformation of unequal structural relations. The problem question to be answered is: How did the perceptions of social relations perceptions of the popular classes of Haiti interfere / interfere in the constitution of a political movement between 1986 and 2018 that would transform the social order in that country? Thus, we formulate the hypotheses that: The Haitian peasantry, the majority of the urban categories, largely excluded from the formal labor market and without significant school capital showed patterns of perceptions of social relations inherited from peasant life reinforced by religious morality - deprived of the possibility of conceiving society as a space of objective struggles. The approach of this research will be qualitative, with an exploratory phase followed by a description. The literature search will support the collection of indirect data. For the direct data, we will develop a semi-structured interview guide to interrogate different subjects of the popular classes in order to collect and analyze their perception of social relations, political and social struggles. The theoretical support is Pierre Bourdieu's genetic structuralist, in particular the categories of habitus and the social fields. Our data confirm that most respondents conceive social relations based on the doxical appropriation of structural relations between classes and the evidence of their humanity, whose request for recognition is the basis of their criticism of the ruling classes. Their views on political and social struggles reveal a lack of awareness of the antagonisms of social fields, expressed by his appeal to unity between politicians and social classes.The statements demonstrated that the appeal to the unity of the classes by the popular categories reflects above all a critique of the individualism of the ruling classes. A community perception of social relations in total logical affinity with the standard of traditional Haitian society that wanted to ban any individualistic spirit from socialized agents within its structures, prioritizing educational strategies that inculcated a full appreciation of the community spirit in individuals for the preservation of this community. Deprived of the means of cultural production of the social world, these classes mobilize their community relations schemes to formulate their judgments of social and political struggles. Its class ethos is totally foreign to the practical logic of capitalist societies. These schemes interfered with the constitution of a popular movement to the extent that these popular classes preferred to reject rather than legitimize heretical discourses that attempt to unravel the structural conflict that unites them with the Haitian oligarchy because they are contrary to their common sense. In short, this interfered with the constitution of a popular movement of transformation of the Haitian social order, because the departure of ethical judgments of these popular classes of struggle made them unable to constitute an effective class, that is, mobilized in confrontation with the oligarchy as an adverse class to fight against.